Alat Sistem Penjemur Ikan Asin Otomatis Berbasis IoT (Internet Of Things) - Herwanto, Prengki Rahmadan; Kalsum, Toibah Umi; Alamsyah, Hendri (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2023)
The fishing industry is currently one of the choices of food ingredients for daily needs. In everyday life, we are familiar with salted fish. To process salted fish, the drying process is done manually so fishermen have to directly control the drying of salted fish using 5-6 fishermen and drying salted fish cannot be left alone because salted fish is very vulnerable to rainwater. To minimize damage to salted fish and make fishermen's work easier, technology for automatic drying of salted fish based on the internet of things has been developed. The components used in making this IoT-based salted fish dryer are NodeMcu, rain sensors, light sensors, and servo motors. This research uses experimental methods, this research was carried out on ANTB (Bengkulu Traditional Fishermen's Alliance) on the coast of Bengkulu. The results of the research, the salted fish drying equipment can be controlled remotely using the Blynk Platform with an ON-OF controller, opening the drying roof by detecting the bright light sensor and closing the drying roof by detecting the rain sensor, then monitoring the drying remotely using the Blynk Platform so that it can determine bright conditions by displaying the LDR sensor value and indicator light for the rain sensor.